On the compositions of the integer-valued random measures - Grigelionis, B. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Б. Григелионис. О композициях целочисленных случайных мер B. Grigelionis. Apie atsitiktinių matų su sveikomis reikšmėmis kompozicijas